2022
DOI: 10.1002/jum.16048
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability in Ultrasound‐Based Liver Fat Quantification

Abstract: Objectives-To assess interobserver variability in ultrasound-based quantitative liver fat content measurements and to determine how much time these quantitative ultrasound (QUS) techniques require.Methods-One hundred patients with known or suspected of having nonalcoholic fatty liver disease were included in this prospective study. Two observers who were blinded to each other measurements performed tissue attenuation imaging (TAI) and tissue scatter distribution imaging (TSI) techniques independently. Both obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The method is available as tissue scatter distribution imaging (TSI, Samsung Medison), and the TSI image acquisition process is similar to that of TAI [ 3 ]. According to the preliminary study data, the method is highly reproducible, operator-independent, and easy to learn [ 32 ]. Similar conclusions were reached in related studies, which also identified a good correlation of both parameters with CAP when assessing the presence of LS [ 33 , 34 ].…”
Section: Ultrasound Methods Used For Ls Evaluationmentioning
confidence: 99%
“…The method is available as tissue scatter distribution imaging (TSI, Samsung Medison), and the TSI image acquisition process is similar to that of TAI [ 3 ]. According to the preliminary study data, the method is highly reproducible, operator-independent, and easy to learn [ 32 ]. Similar conclusions were reached in related studies, which also identified a good correlation of both parameters with CAP when assessing the presence of LS [ 33 , 34 ].…”
Section: Ultrasound Methods Used For Ls Evaluationmentioning
confidence: 99%
“…In particular, the Nakagami distribution correlates backscattering to the percentage of liver fat. In our work, Nakagami distribution is calculated by a parameter, tissue scatter distribution imaging (TSI, Samsung Medison), which calculates the concentration and the distribution of the ultrasound scatterers [ 41 , 42 ].…”
Section: Tissue Scatter Distribution Imaging (Tsi Samsung Medison)mentioning
confidence: 99%
“…However, the sensitivity of ultrasonography is limited when hepatic steatosis content is below a certain threshold [ 59 ]. Traditional ultrasonography uses semi-quantitative ordinal classifications for liver fat, such as mild, moderate, and severe, which exhibit limited inter-observer agreement [ 76 ]. In contrast, contemporary quantitative ultrasound techniques offer enhanced performance using quantitative data derived from acoustic parameters of liver tissue.…”
Section: Introductionmentioning
confidence: 99%